Stages and Procedures for Marriage According to the Customs of Kuantan Singingi Regency, Riau - Melliofatria; Faizah, Hasnah; Rahman, Elmustian; Hermandra; Corrina, Fatti; M, Sarjan (MultiTech Publisher, 2024)
The study aims to describe the stages and procedures of marriage according to customs in Kuantan Singingi district, Riau. This type of research is descriptive qualitative. The subjects of the study were village heads, community leaders, ninik mamak and 30 residents of Kuantan Singingi regency, Riau. Data collection tools use checklists and interview guidelines. Data analysis techniques use descriptive analysis. The results showed that there are various stages of different customs in each sub-district in Kuantan Singing regency and several factors that cause changes in the implementation of the customary stages in marriage in Kuantan Singingi regency, Riau.